EFEKTIVITAS EKSTRAK TUMBUHAN RAWA SEBAGAI INSEKTISIDA NABATI TERHADAP HAMA ULAT TRITIP PlutellaXylostella SKALA LABORATORIUM : (Effectiveness Of Swamp Plants Extract As A Botanical Insecticide on Diamondback Moth Plutella Xylostella Laboratory Scale) - Syaiful Asikin; Melhanah, Melhanah (Fakultas Pertanian Universitas Palangka Raya, 2023)
ABSTRACT Diamondback Moth (Plutella xylostella) can attack the shoots and leaves of plants belonging to the Cruciferae family (cabbage, mustard greens, caisin) from seedling to harvesting. The part of the plant that it attacks is the leaf with symptoms of holes. In general, in controlling pests, farmers always partner with chemical insecticides, while in the concept of integrated pest management (IPM), the use of chemical insecticides is the last alternative. To overcome this, pest control is directed to the use of plants as botanical insecticides. From the research, it was found that 9 types of swamp plants had a value of 84.00% that killed the tritip caterpillar, and 3 types that killed 81-82%. The LD50 value of the caterpillar in 10 swamp plant species was classified as moderately toxic (Galam, Cambai Karuk, Gandarusa grass, Pegagan grass, Tawar, Tegari, Melinjo, Kipahit, Maja and Tapak Liman), and 3 other types of swamp plants were mildly toxic ( Jingah, Bidara and Tanduk Rusa). Thus, it is necessary to preserve swamp wild plants so that these plants do not become extinct. Keywords: Plutella xylostella, swamp plant, botanical insecticide,